Efficacy of Co-administration of Liuwei Dihuang Pills and Ginkgo Biloba Tablets on Albuminuria in Type 2 Diabetes: A 24-Month, Multicenter, Double-Blind, Placebo-Controlled, Randomized Clinical Trial - Shi, Ruifeng; Wang, Yanping; An, Xiaofei; Ma, Jianhua; Wu, Tongzhi; Yu, Xiaojin; Liu, Su; Huang, Liji; Wang, Lijuan; Liu, Jingshun; Ge, Jing; Qiu, Shanhu; et al. (Frontiers in Endocrinology, 2019)
Purpose: We investigated the effects of Traditional Chinese Medicine (TCM) on the occurrence and progression of albuminuria in patients with type 2 diabetes. Methods: In this randomized, double-blind, multicenter, controlled trial, we enrolled 600 type 2 patients without diabetic nephropathy (DN) or with early-stage DN. Patients were randomly assigned (1:1) to receive Liuwei Dihuang (LWDH) (1.5 g daily) and Ginkgo biloba (24 mg daily) orally or matching placebos for 24 months. The primary endpoint was the change in urinary albumin/creatinine ratio (UACR) from baseline to 24 months. Results: There were 431 patients having UACR data at baseline and 24 months following-up in both groups. Changes of UACR were not affected in both groups: -2.06+26.79 (from 21.06+23.34 to 19.00+19.89 mg/g) in TCM group and 4.99+53.99 (from 20.62+27.91 to 25.61+51.67 mg/g) in control group. For patients with UACR>30mg/g at baseline, LWDH and Ginkgo biloba significantly reduced the UACR value at 24 months (56.92+33.89 vs. 31.15+32.23, P<0.05). Moreover, the change of UACR value between baseline and follow-up in TCM group was more significant than that in control group (-25.77+46.73 vs. -3.66+104.88, P<0.05). Conclusion: LWDH and Ginkgo biloba may attenuate deterioration of albuminuria in type 2 patients. These results suggest that TCM is a promising option of renoprotective agents for early stage of DN. Trial registration: The study was registered in the Chinese Clinical Trial Registry. (no. ChiCTR-TRC-07000037, chictr.org)